Acts Against the Law in the Field of Investment in Indonesia - ., Nofriza; Murwadji, Tarsisius; Lita, Helza Nova (Journal of Ecohumanism, 2025)
The world of investment involves several aspects, both financial and non-financial. It is not uncommon for investments between countries to involve government officials who, in certain cases, commit acts of abuse of power. The act in question in this case will be explored in the theory of Economic Analysis of Law and also as regulated in Article 1365 of the Civil Code. The research metode involves literature research conducted through a literature review. This study finds that the implementation of Legal Quality Audit in the field of investment is an appropriate strategy because it can be carried out at the pre-investment stage, investment execution stage, and investment accountability stage. With Legal Quality Audit, the potential for unlawful acts in investment can be detected, from the pre-investment phase to the conclusion of the investment agreement. There are also two important aspects of which are Concept (philosophical foundation) and Parameter (quantitative aspect). It leads to the Legal Quality Audit System, which measures multidisciplinary quality parameters. Also, The Legal Quality Audit can be applied at various stages of investment to detect potential unlawful acts, ensuring reliability, customer satisfaction, and adherence to legal obligations.